Creative branding strategies in Indonesia’s cryptocurrency industry: Evidence from Indodax - Faqih, Muhammad Ariq; Setiadi, Anggi Arif Fudin (Communications in Humanities and Social Sciences, 2025)
The global popularity of cryptocurrency has increased significantly, yet in Indonesia it still faces challenges such as negative stigma, regulatory uncertainty, and intense competition. This study analyzes Indodax’s creative strategy in developing its brand image within Indonesia’s growing cryptocurrency industry. A qualitative case study approach was employed to collect data through in-depth interviews, social media content analysis (Instagram, TikTok, and YouTube), and a study on product placement in the film 13 Bom di Jakarta. The findings of the study indicate four key strategies. Firstly, public education through being engaged in social media content such as tutorials, infographics, and expert discussions serves to enhance digital literacy. Secondly, data-driven marketing fosters interaction and audience engagement. Thirdly, product placement in film has been demonstrated to enhance brand exposure and emotional resonance through integrated visual and narrative elements. Fourthly, transparency and regulatory compliance are emphasized through clear communication, thus reinforcing public trust. These strategies collectively facilitate Indodax to shape its brand as a reliable and innovative platform in the face of industry challenges.